2020
DOI: 10.1038/s41388-020-1382-5
|View full text |Cite
|
Sign up to set email alerts
|

β-catenin S45F mutation results in apoptotic resistance

Abstract: Wnt/β-catenin signaling is one of the key cascades regulating embryogenesis and tissue homeostasis; it has also been intimately associated with carcinogenesis. This pathway is deregulated in several tumors, including colorectal cancer, breast cancer, and desmoid tumors. It has been shown that CTNNB1 exon 3 mutations are associated with an aggressive phenotype in several of these tumor types and may be associated with therapeutic tolerance. Desmoid tumors typically have a stable genome wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Previous studies suggested the contribution of this genetic alteration to resistance to targeted therapy [ 24 ] as well as immunotherapy [ 25 ]. The potential mechanism of melanoma insensitivity to treatment may involve resistance of the mutated cells to apoptosis [ 26 ]. A TP53 mutation may also impair a response to targeted therapy [ 27 ] and immunotherapy [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested the contribution of this genetic alteration to resistance to targeted therapy [ 24 ] as well as immunotherapy [ 25 ]. The potential mechanism of melanoma insensitivity to treatment may involve resistance of the mutated cells to apoptosis [ 26 ]. A TP53 mutation may also impair a response to targeted therapy [ 27 ] and immunotherapy [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, binding of Wnt ligands initiates this canonical pathway, inducing translocation of the nuclear localization of beta-catenin and activating wnt downstream targets to potentiate cell growth, adhesion and survival (45). Deregulated expression of wnt/beta-catenin has been reported in different cancer progression and therapeutic tolerance (46)(47)(48). In addition, dysregulation of apical junction is tightly connected with EMT (49), which contributes to the flexibility of cell motility and tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that β-catenin-TCF/LEF interaction in cytoplasm can promote the transcription of downstream target genes and causes abnormal proliferation and differentiation of cells, thus promoting the occurrence of cancer (17,18). Actually, the site mutation of CTNNB1 always associate with the changes of CTNNB1 biological function in various humane diseases (19)(20)(21). A previous study shows that the CTNNB1 mutations trigger the high expression of Wnt signaling pathway, which further contribute to the development of LUAD (22).…”
Section: Original Articlementioning
confidence: 99%